2019
DOI: 10.1371/journal.pone.0223925
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial efficacy of cold atmospheric plasma against Enterococcus faecalis planktonic cultures and biofilms in vitro

Abstract: Nosocomial infections have become a serious threat in our times and are getting more difficult to handle due to increasing development of resistances in bacteria. In this light, cold atmospheric plasma (CAP), which is known to effectively inactivate microorganisms, may be a promising alternative for application in the fields of dentistry and dermatology. CAPs are partly ionised gases, which operate at low temperature and are composed of electrons, ions, excited atoms and molecules, reactive oxygen and nitrogen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 63 publications
0
30
0
Order By: Relevance
“…The reduction values for devices utilizing ambient air in all time intervals were demonstrated by two of the studies. The application of 60 s led to results ranging from no reduction to 7.9 log 10 reduction units [ 55 ]. For pure helium plasma, outcomes ranged from no reduction [ 45 ] to no detection of CFU within 60 s [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction values for devices utilizing ambient air in all time intervals were demonstrated by two of the studies. The application of 60 s led to results ranging from no reduction to 7.9 log 10 reduction units [ 55 ]. For pure helium plasma, outcomes ranged from no reduction [ 45 ] to no detection of CFU within 60 s [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lower concentrations of S. mutans and L. acidophilus resulted in an increased inactivation [ 21 , 28 , 32 ]. In general, biofilm maturation was associated with an augmented resistance to CAP application in Gram-positive [ 22 , 24 , 31 , 55 ] and Gram-negative species [ 31 ]. The maturation of the biofilm is accompanied with the production of an extracellular matrix and an increase of biofilm thickness.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that wound environmental factors such as biofilm formation and wound exudate could have played a role in the limited efficacy of CAP in vivo. It was shown that bacteria in biofilms can be more tolerant against CAP [ 43 45 ]. Additionally, bacterial colonization and wound exudate could increase pH and/or introduce buffering effects to the wounds [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cold atmospheric plasma (CAP) is a partly ionized gas containing free radicals, ions, electrons and photons which are produced due to the electric field action [ 50 , 51 ]. Due to the light component (photons) it may be considered light-based therapy.…”
Section: State Of the Artmentioning
confidence: 99%
“…The principal mecha-nisms of CAP involve cell membrane permeabilization, activity of reactive oxygen and ni-trogen species as well as the chemical reactions leading to DNA damage [ 54 ]. CAP was demonstrated to be an efficient bactericidal treatment leading to Bacillus subtilis and Clos-tridium difficile spores inactivation [ 55 ], eradication of MRSA and E. coli in in vitro porcine skin model [ 56 ], as well as inactivation of other Gram-positive and Gram-negative species [ 51 , 53 , 57 ]. A study aimed at investigating the development of CAP tolerance was described by Matthes et al, employing S. aureus biofilm culture in medium to mimic an artificial wound environment.…”
Section: State Of the Artmentioning
confidence: 99%